The lost of old Demak Sultanate city pattern - Rukayah, Siti; Giovano, Fariz Addo; Abdullah, Muhammad (Journal of Architecture and Urbanism, 2023)
This article reveals that the problem of sedimentation on the coast causes the loss of the old city. Sedimentation caused the Demak sultanate (1478–1586) no longer be on the coast and lose its power as a Maritime kingdom. What was the old Demak city shape? Historical records state that the strait had become a swamp and experienced frequent flooding. After going through three generations from 1478–1546, the fourth king moved the Demak to Prawata Hill (1546– 1549 AD). Due to the lack of maps and historical data, we analyze the old Demak using maps and pictures of contemporary Javanese sultanate cities such as Cirebon (1506-present) and Banten (1526–1815). We also use its predecessor kingdom, Majapahit (1293 to 1527 AD) as a reference and the successor sultanate as an analytical tool. The long-lasting sultanate had a city centre that grew and developed with complete urban facilities and infrastructure. The sultanate had a short life; the city core was still intact as the city nucleus, like Demak. Due to geological problems, the king needed more time to complete the city plan with city facilities. Demak was a transitional city from the Hindu/Buddhist-Islamic concept and coastal city to the inland concept.